Design and fabrication of automated mini forklift / Fatin Nabila Mohd Zaki - Mohd Zaki, Fatin Nabila (2023)
In this project, an attempt has been made to design and fabricate aa automated mini forklift which helps human to lift loads from one place to a higher place. The main purpose of designing an automated mini forklift is to operates it on automated basis without requiring any human power to lift it. Forklifts are widely used in industry, so this initial target for this project will lead to industry people. The mini forklift uses a linear actuator to lift loads and a motor to lift weights. The lifting mechanism is attached to a 4-wheel drive frame chassis, powerful enough to serves as a counterweight and support for the frame.